Pemberdayaan Ekonomi Kaum Perempuan GMIT Genezaret Danau Ina Lasiana dalam Pengolahan Keripik Pisang Coklat - Helda Marlin Ala; Yudith Febrianty Lerrich (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Empowerment is an effort to enhance the capabilities of individuals or groups so that they can perform tasks and responsibilities according to performance demands. Empowerment aims to help them meet basic needs, access productive resources, increase income, and participate in development. In the modern context, women are not only acting as housewives but also contributing in social and economic fields, working outside the home to support household expenses and improve family status. This shifts the role of women from the domestic sector to the public. Housewives have significant responsibilities in managing the household and ensuring family nutrition, which is crucial for achieving optimal health. Bananas, as a tropical fruit with high economic value, offer many health benefits, including preventing blood sugar spikes, improving digestion, supporting diet programs, and having various other benefits that are not widely known by the public.